Advanced solid state physics - Phillips, Philip (Philip W.) (Cambridge University Press, 2012)
"Providing an up-to-date and lucid presentation of phenomena across modern advanced-level solid state physics, this new edition builds on a basic understanding to introduce students to the key research with the minimum of mathematics. It covers cutting-edge topics, including electron transport and magnetism in solids. It is the first book to explain topological insulators and strongly correlated electrons. Explaining solid state physics in a clear and detailed way it also has 100 exercises for students to test their knowledge. In addition to the extensive discussion of magnetic impurity problems, bosonization, quantum phase transitions and disordered systems from the first edition, the new edition includes such topics as topological insulators, high-temperature superconductivity and Mott insulators, renormalization group for Fermi liquids, spontaneous symmetry breaking, zero and finite-temperature Green functions, and the Kubo formalism. Figures from the book and solutions to student exercises are available online at www.cambridge.org/solidstate"-- Provided by publisher.